Struktur Populasi Hirangan (Trachypithecus cristatus) di Desa Beringin Kencana Kabupaten Barito Kuala - Annisa Aliffira Syaumi; Mahrudin Mahrudin; Riya Irianti (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Beringin Kencana is a village located in Barito Kuala Regency, South Kalimantan Province. The Beringin Kencana area contains mangrove areas, swamp forests, rice fields, settlements and oil palm plantations. The Beringin Kencana area, which is located on the border of the Barito Kuala and Central Kalimantan regions, is an area that has not been widely publicized, especially the diversity of flora and fauna that exist, so it needs to be introduced to the public widely. The results showed that the population of Hirangan in Beringin Kencana Village was obtained from adults 2.61 individuals/Ha, young 1.07 individuals/Ha and tillers 1.90 individuals/Ha. Pyramid on the population structure of hirangan in Banyan Kendi village is in the form of an urn/kendi. Pyramid shaped caddy shows that the number of young people is less than the number of adults.